800 words. Season 1 [videorecording (DVD)] - Amenta, Pino; Smith, Mike; Thompson, Erik, 1959-; Vidler, Melinda; Anthony, Benson Jack, 1997- (Acorn Media, 2016)
George Turner, a recent widower, quits his job as a popular 800-word columnist for a Sydney newspaper. On an impulse, he buys a house online in a remote seaside town in New Zealand. He then has to break the news to his two teenage kids, Shay and Arlo, who just lost their mom and now face an even more uncertain future. When the family arrives in their new home, the colorful and inquisitive locals ensure Turner's dream of a fresh start does not go according to plan.